Servant leadership, work-life quality, and organizational citizenship behavior in nurses: a cross-sectional design - Mina Mohammadpour Bayati; Amir Sadeghi; Mehrdad Maleki Jamasbi; Leili Tapak (BMC Nursing)
Abstract Background Organizational citizenship behavior and quality of work life of nurses are influential factors in improving health care services provided by nurses. The leadership style of head nurses is a key factor in enhancing nurses’ performance. This study aimed to explore the relationship between head nurses’ servant leadership style and both the quality of work-life and organizational citizenship behaviors among nursing staff. Methods This cross-sectional and correlational study encompassed 344 nurses from five hospitals affiliated with Hamadan University of Medical Sciences in Iran. These nurses were chosen through stratified proportional random sampling between December 2021 and April 2022. Data were collected using questionnaires assessing demographics, servant leadership, quality of work-life, and organizational citizenship behaviors. Statistical analysis was performed using SPSS v.20, employing descriptive statistics and inferential methods, specifically independent sample t-test, Pearson correlation coefficient and multiple regression analysis. Results The majority of nurses indicated a moderate level of quality of work life (64.5%) as well as organizational citizenship behavior (65.4%). The findings demonstrated a strong and statistically significant correlation between servant leadership style and both quality of work-life (r = 0.680, p = 0.001) and organizational citizenship behavior (r = 0.727, p = 0.001). Furthermore, a positive and moderate to strong correlation was found between organizational citizenship behavior and quality of work-life (r = 0.583, p = 0.001). Servant leadership style (β = 0.663, P < 0.001), quality of working life (β = 0.160, P = 0.001), gender (β = 0.126, P = 0.011), and work shift (β = 0.112, P = 0.041) all positively and significantly influenced nurses’ organizational citizenship behavior, accounting for approximately 55% of its variability. Conclusions This study confirmed the relationship between head nurses’ servant leadership style and both quality of nurses’ work-life and the organizational citizenship behavior. It is recommended that healthcare system managers prioritize training head nurses in the servant leadership style and encourage them to use this leadership style to enhance the quality of work life and organizational citizenship behavior of nurses.